HST/STIS abundances in the uranium rich metal poor star CS 31082-001: Constraints on the r-Process. Issue 1 (January 2016) - Siqueira-Mello, C; Spite, M; Barbuy, B; Spite, F; Caffau, E; Hill, V; Wanajo, S; Primas, F; Plez, B; Cayrel, R; Andersen, J; Nordström, B; et al.
Abstract: As a brief revision, the origin of heavy elements and the role of abundances in extremely metal-poor (EMP) stars are presented. Heavy element abundances in the EMP uranium-rich star CS 31082-001 based mainly on near-UV spectra from STIS/HST are presented. These results should be useful for a better characterisation of the neutron exposure(s) that produced the r-process elements in this star, as well as a guide for improving nuclear data and astrophysical site modelling, given that the new element abundances not available in previous works (Ge, Mo, Lu, Ta, W, Re, Pt, Au, and Bi) make CS 31082-001 the most completely well studied r-II object, with a total of 37 detections of n-capture elements.